1999
DOI: 10.1210/en.140.3.1082
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary and Testicular Function in Growth Hormone Receptor Gene Knockout Mice

Abstract: The role of GH in the control of pituitary and testicular function is poorly understood. GH receptor gene knockout (GHR-KO) mice were recently produced. As these mice are good experimental animals to assess the influence of the effects of GH and insulin-like growth factor-I (IGF-I), the present studies were undertaken. Young adult male GHR-KO mice and their normal siblings were tested for fertility and subsequently injected (i.p.) with saline or GnRH (1 ng/g BW) in saline. Fifteen minutes later, blood was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 0 publications
5
98
0
Order By: Relevance
“…The infertility in female mice transgenic for the PEPCK.bGH gene construct is due to luteal failure, which in turn appears to be caused by inadequate PRL secretion after mating [61]. In studying the GH receptor gene knockout (GHR-KO) mice, Chandrashekar et al found that the circulating LH response to GnRH treatment was significantly attenuated, and basal and LH-stimulated testosterone release from the isolated testes of GHR-KO mice were decreased [62]. In GH receptor (GHR) and GH-binding protein (GHBP) knockout (KO) mice, the number of follicles per ovary was markedly reduced, and both the reproductive function and ovulation rate are measurably decreased compared with wild-type animals.…”
Section: Reproductive Fitness Traits Of Gh Transgenic Fishmentioning
confidence: 99%
“…The infertility in female mice transgenic for the PEPCK.bGH gene construct is due to luteal failure, which in turn appears to be caused by inadequate PRL secretion after mating [61]. In studying the GH receptor gene knockout (GHR-KO) mice, Chandrashekar et al found that the circulating LH response to GnRH treatment was significantly attenuated, and basal and LH-stimulated testosterone release from the isolated testes of GHR-KO mice were decreased [62]. In GH receptor (GHR) and GH-binding protein (GHBP) knockout (KO) mice, the number of follicles per ovary was markedly reduced, and both the reproductive function and ovulation rate are measurably decreased compared with wild-type animals.…”
Section: Reproductive Fitness Traits Of Gh Transgenic Fishmentioning
confidence: 99%
“…Inactivation of the GHR gene results in severe postnatal growth retardation, greatly decreased levels of IGF-1, and elevated levels of circulating GH. 1,2 The transcription factors Stat5a and Stat5b are highly conserved and serve overlapping and mostly redundant roles. However, pubertal growth of Stat5b Ϫ/Ϫ males, but not females, is reduced.…”
mentioning
confidence: 99%
“…The reduced testicular growth and possible impairment of spermatogenesis could be due to the reduced levels of plasma FSH seen in the GHR/BP j/j mice (Chandrashekar et al 2001). Basal levels of plasma LH and testosterone were similar in GHR/BP j/j and +/+ male mice, but the LH and testosterone responses to administration of a single dose of gonadotropin releasing hormone were significantly attenuated in the GHR/BP j/j mice (Chandrashekar et al 1999). Intratesticular levels of testosterone were essentially the same between GHR/BP j/j and +/+ males, but the basal in vitro release of testosterone by salinetreated testes obtained from GHR/BP j/j mice was significantly less than for saline-treated testes obtained from +/+ mice, as was the testosterone response to LH treatment, either by the isolated testes or by the intact animal (Chandrashekar et al 1999(Chandrashekar et al , 2001.…”
Section: Reproductive Functionmentioning
confidence: 95%
“…Absolute weights of the pituitary, testis, seminal vesicle, ventral prostate and epididymis were dramatically decreased, despite significantly increased levels of circulating prolactin (Keene et al 2002;Chandrashekar et al 1999 and. Fertility was also decreased, perhaps as a result of the hyperprolactinemia, although the number of testicular PRL receptors was decreased (Chandrashekar et al 1999 and.…”
Section: Reproductive Functionmentioning
confidence: 99%